Analisis Kelayakan Usaha Tani Hidroponik Bayam (Amaranthus tricolor) (Studi Kasus: Sufi Agrifarm, di Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang) - Siti Zubaidah Sitorus; Ahmad Rafiqi Tantawi; Khairul Saleh (Mahesa Research Institute, 2023)
This study aims to determine the income and feasibility of hydroponic spinach farming and whether spinach hydroponic farming is feasible. This research was conducted from November to December 2020. The location of the research was determined purposively because it took into account where there had been a lot of conversion of agricultural land to non-agriculture. The population in this research is Sufi Agrifarm's hydroponic spinach farming, the data used is primary data. The analysis used in this study is income and feasibility analysis, in the feasibility analysis used the formula R/C B/C and BEP (Break Even Point). Amaranth hydroponic farming income is Rp. 25.153.166,67/month. The value of R/C Ratio hydroponic farming of spinach 2.64 1 and B/C 1.64 1 with a break-even point of spinach production of 171 kg 450 kg and a break-even point of Rp. 34.104/Kg Rp. 90,000 and can be said to be decent.